The Influence of Ethnic Identity and Brand Trust on College Choice Decisions (Case Study at IT&B Campus) - Nasib (Journal of Business Integration Competitive, 2024)
This study seeks to examine the impact of ethnic identity and brand trust on the choice to enroll in an IT&B institution. Ethnic identification significantly influences individual preferences, particularly in educational choices. Brand trust denotes the degree to which potential students rely on the reputation and quality provided by educational institutions. This research adoperguruan tinggi swasta a quantitative approach, employing a survey method with prospective IT&B students as participants. We performed data analysis employing various linear regression methods to examine the impact of independent factors on the dependent variable. The study's findings demonstrate that ethnic identification and brand trust substantially affect prospective students' choices about an IT&B campus for their education. These findings have practical implications for marketing tactics in higher education, particularly in enhancing brand trust among various ethnic groups.